Answer:
[tex]\frac{64}{q^{4}}[/tex]
or
[tex]64q^{-4}[/tex]
Step-by-step explanation:
Remember the properties
Product rules
[tex]a^{n} a^{m}=a^{n+m}[/tex]
Power rules
[tex](a^{n})^{m}=a^{n*m}[/tex]
we have
[tex](-2p^{-5}q4p^{5}q^{-3})^{2}[/tex]
Applying the product rules
[tex](-2(4)p^{-5+5}q^{-3+1})^{2}[/tex]
[tex](-8p^{0}q^{-2})^{2}[/tex]
[tex](-8q^{-2})^{2}[/tex]
Applying the power rules
[tex]64q^{-4}[/tex]
[tex]\mathrm{Apply\:exponent\:rule}:\quad \:a^{-b}=\frac{1}{a^b}[/tex]
[tex]64q^{-4}=\frac{64}{q^{4}}[/tex]